Investigating the partial structure of the hydrate film formed at the gas/water interface by Raman spectra. (16th March 2017) - Zeng, Xin-Yang; Zhong, Jin-Rong; Sun, Yi-Fei; Li, Sheng-Li; Chen, Guang-Jin; Sun, Chang-Yu
Abstract: The morphology and structure of hydrate films of pure methane and methane+ethane mixtures were studied by suspending a single gas bubble in liquid water. The methane+ethane gas mixtures, containing 20 mol% or 81–89 mol% methane, were used to form hydrate films with different crystal structures. Polyhedral structures appeared on the background of uniform polycrystalline hydrate films formed by gas mixtures with a high methane mole fraction of 0.81–0.82. Some of the polyhedral structures are holes, and others are separated structure II polyhedral hydrate crystals. However, for pure methane, a gas mixture with a lower CH4 mole fraction of 0.2, or a gas mixture with a higher CH4 mole fraction of 0.89, the morphology is uniform through the whole hydrate film. The crystal structures in the hydrate film were determined using in situ Raman spectra. The results show that both pure methane and the gas mixture with a lower CH4 mole fraction of 0.2 form a hydrate film with structure I. The single polyhedral crystal appeared in the background of the uniform polycrystalline hydrate film formed by gas mixtures with a high methane mole fraction of 0.81–0.82 as a structure II CH4 -C2 H6 double hydrate crystal. The hole is mainly gas with an initial small amount of structure I hydrate, and that hole will be filled with structure II hydrate after a certain time. The experimental methods and the new findings presented in this work should be significant for the further research of hydrate growth kinetics. Highlights: Morphology and partial structure of hydrate film on gas bubble surface were studied. Part of polyhedral structures are holes and others are separated single crystals. Polyhedral structures appeared for CH4 -C2 H6 mixture with 81–82% methane. Single polyhedral crystals and holes after filled with hydrate are sII hydrate.